The Effectiveness Implementation Team Games Tournament Learning Model on Negotiation Text Materials Class X Students - Khasanah, Lailatul; Suwadi, Suwadi; Sugianti, Sugianti (Actual Insight, 2025)
This study investigates the effectiveness of the Team Games Tournament learning model as a cooperative learning strategy in teaching negotiation texts to Grade X students at Muhammadiyah 1 Vocational High School Pasuruan. The research was motivated by initial classroom observations indicating low student enthusiasm and passive learning behavior, particularly regarding negotiation texts. This study employed a qualitative descriptive approach, involving 33 students. Data were collected through classroom observations, teacher and student questionnaires, and documentation of learning outcomes. Data analysis followed the Miles and Huberman model: data reduction, display, and conclusion drawing. The findings reveal that the Team Games Tournament model significantly increased student engagement, collaboration, and confidence. Approximately 90% of students actively participated in role-play activities and demonstrated improved comprehension of negotiation texts. Teachers also reported enhanced classroom interaction and ease of implementation. The Team Games Tournament model fostered a dynamic, competitive, and cooperative environment, aligning with vocational education's emphasis on practical and interpersonal skills. These results suggest that Team Games Tournament is a viable alternative for promoting active learning in language subjects, particularly in vocational school contexts.